EFFECT OF LUTEIN IN HYPERCHOLESTEROLEMIA INDUCED OXIDATIVE STRESS IN MALE WISTAR RATS - K., Soundarya Priyadharsini; P., Nirmala; P., Ashok Kumar (International Journal of Current Pharmaceutical Research, 2015)
Objective: Oxidative stress induced by reactive oxygen species (ROS) plays an important role in the etiology of several diseases, including atherosclerosis and coronary heart disease. Hypercholesterolemia is reported to be associated with the oxidative stress that results from the increased production of ROS or impairment of the antioxidant system. Hence the objective of this study was to evaluate the antioxidant effect of lutein in hypercholesterolemiainduced oxidative stress in male wistar rats. Methods: Male Wistar rats were divided into 6 groups of 6 each. Group I served as control. Group II III, IV, V & VI rats were received high cholesterol diet. Group III was treated with Atorvastatin 5 mg/kg. Group IV, V & VI rats was treated with 25 mg/kg, 50 mg/kg & 100 mg/kg of Lutein. After 16 weeks, blood samples &liver tissue samples were collected from all the groups of animals to evaluate antioxidant levels in blood & tissue samples. Results: Catalase, superoxide dismutase, glutathione peroxidase, glutathione levels significantly increased in both plasma & liver in lutein treated groups. TBARs level is increased in plasma in hypercholesterolemicrats and Malondialdehyde level in the liver tissue is also significantly increased in hypercholesterolemic rats. Conclusion: The results of this study indicate Lutein is an effective nutritional supplement to prevent oxidative stress in hypercholesterolemia.